2017
DOI: 10.1002/jccs.201600817
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticle‐modified Glassy Carbon Electrode as a Highly Sensitive Electrochemical Sensor for the Detection of Caffeine

Abstract: Zinc oxide nanoparticles (ZnO NPs) were prepared by a simple, convenient, and cost‐effective wet chemical method using the biopolymer starch. The prepared ZnO NPs were characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), energy‐dispersive X‐ray (EDX), Fourier transform infrared (FT‐IR), and UV‐visible spectroscopic techniques. The average crystallite size calculated from XRD data using the Debye–Scherer equation was found to be 15 nm. The electrochemical behavior of caffeine (CAF) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…As a result, the following study focuses on the Z-660-(5 h) sample. As can be seen in Figure 7(a), no typical absorption bands for meIm are observed; instead, the absorption band at 400-550 cm -1 corresponding to the stretching vibration of Zn-O [17,21,31] confirms the formation of ZnO. This result is consistent with that of X-ray diffraction shown in Figure 5(b).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As a result, the following study focuses on the Z-660-(5 h) sample. As can be seen in Figure 7(a), no typical absorption bands for meIm are observed; instead, the absorption band at 400-550 cm -1 corresponding to the stretching vibration of Zn-O [17,21,31] confirms the formation of ZnO. This result is consistent with that of X-ray diffraction shown in Figure 5(b).…”
Section: Resultssupporting
confidence: 87%
“…Zinc oxide (ZnO) is an n-type semiconductor with a wide bandgap (3.37 eV) and a large excitation binding energy (60 meV) at room temperature [21][22][23][24][25]. This material has unique electrical and photovoltaic properties, so it has been studied and applied in the fields of photocatalysis, gas sensing, medicine, electrochemistry, and solar cells [21][22][23][24][26][27][28][29][30][31][32]ZnO has extremely rich morphologies, depending on the synthesis method, such as spheres [27,30], nanorods [28], nanowires [29], and flower-shaped nano [32].…”
Section: Introductionmentioning
confidence: 99%
“…19 Among the EC methods, the electrochemical approach has drawn signicant attention of researchers due to its high sensitivity, good selectivity, inexpensive instruments, ease of operation, simple pretreatment of samples, and faster analysis. To improve the sensitivity and avoid the multi-selectivity, the electrodes have been modied with various semi-conductive metal oxides such as ZnO, [20][21][22] Cr 2 O 3 , 23 SnO 2 , 24 WO 3 , 25 and Co 3 O 4 to detect numerous toxic chemicals and biochemicals. 26 In the recent years, few research studies based on semi-conductive metal oxides have been reported for the reliable detection of CBZs.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the solvent extraction method is generally adopted for the separation of caffeine and by‐product salt in industrial production . Chloroform is an effective extractant, but it is volatile in use, resulting in a significant loss per year and also affecting the health of practitioners.…”
Section: Introductionmentioning
confidence: 99%